2022
DOI: 10.3390/ijms232314961
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic System Establishment between Piriformospora indica and Glycine max and Its Effects on the Antioxidant Activity and Ion-Transporter-Related Gene Expression in Soybean under Salt Stress

Abstract: The utilization of symbiosis with beneficial microorganisms has considerable potential for increasing growth and resistance under abiotic stress. The endophytic root fungus Piriformospora indica has been shown to improve plant growth under salt and drought stress in diverse plant species, while there have been few reports of the interaction of P. indica with soybean under salt stress. In this study, the symbiotic system of P. indica and soybean (Glycine max L.) was established, and the effect of P. indica on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In saline soil, the redox balance within soybean plants is disrupted, resulting in excessive production of reactive oxygen species and triggering oxidative stress responses that damage cell membranes and organelles [16]. Moreover, the imposition of salt stress disrupts the crucial processes of water and nutrient absorption in the intricate root architecture of soybeans, particularly concerning essential metal cations, thereby precipitating imbalances in nutrient distribution [17,18]. This disruption affects physiological metabolic processes in soybeans, inhibiting photosynthesis, respiration and nitrogen metabolism, thereby limiting plant growth and development [19].…”
Section: Introductionmentioning
confidence: 99%
“…In saline soil, the redox balance within soybean plants is disrupted, resulting in excessive production of reactive oxygen species and triggering oxidative stress responses that damage cell membranes and organelles [16]. Moreover, the imposition of salt stress disrupts the crucial processes of water and nutrient absorption in the intricate root architecture of soybeans, particularly concerning essential metal cations, thereby precipitating imbalances in nutrient distribution [17,18]. This disruption affects physiological metabolic processes in soybeans, inhibiting photosynthesis, respiration and nitrogen metabolism, thereby limiting plant growth and development [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll is a key photosynthetic pigment, and increasing its content helps improve the efficiency of plant photosynthesis, carbon fixation capacity, and stress resistance, thereby promoting plant growth [ 40 ]. Numerous studies have indicated that P. indica colonization can increase the chlorophyll content of plants such as Anthurium [ 41 ], soybeans [ 42 ], and Torreya grandis cuttings [ 43 ]. P. indica can enlarge the leaf area of Tartary buckwheat, thereby enhancing its photosynthesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription levels of genes such as OsNAC1, OsNAC6, OsBZIP23, and OsDREB2A are upregulated in rice seedling leaves colonized by P. indica, contributing to enhanced salt tolerance [51]. Moreover, P. indica colonization positively regulates the transcript levels of PMH + ATPase, SOS1, and SOS2, thereby improving soybean growth and salt tolerance [52]. Epigenetic studies have found that P. indica-colonization conferred maize greater salinity tolerance by increasing methylation levels in leaves and changing DNA methylation [53,54].…”
Section: P Indica Mediates Plant Tolerance To Salinity Stressmentioning
confidence: 99%